The Wisdom of Syarî‘ah Al-Ahwal Al-Sakhsiyyah According To Ali Ahmad Al-Jurjawi - Hadi, Nur; Al-Muzakir, Al-Muzakir (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2018)
Ali Ahmad al-Jurjawi, a prominent scholar of wisdom and philosophy, looks at his fundamental and phenomenal work called Hikmat al-Tasyrî‘ wa Falsafatuhu. The study aims to determine the wisdom of family law sharia according to Ali Ahmad al-Jurjawi. This research is library research, where the primary data is the Hikmat al-Tasyrî‘ wa Falsafatuhu, the secondary source of the books relating to the discussion of Islâmic wisdom (maqâṣid) and the philosophy of Islamic law. The data is analyzed by the ushuliyyah method with the measuring instrument maqâṣid al-syarî’ah. The results of his research on the wisdom of sharia in family law (ahwal al-sakhssiyah) is to uphold the goodness and benefit of the servant in making it hard to strengthen the ukhuwah Islâmiyah framed moral values ​​in the household for the sake of the sakinah, mawaddah, and rahmah in the world and the hereafter, always holding fast to the nature of the goal of sharia in reciting the servant, which is to pair with one another and to complement each other so that the peace of life in the household and family can be realized, both husband and wife and children and the extended family among them.